Standardized Prevalence Ratios for Atrial Fibrillation in Adult Dialysis Patients in Japan - Ohsawa, Masaki; Tanno, Kozo; Okamura, Tomonori; Yonekura, Yuki; Kato, Karen; Fujishima, Yosuke; Obara, Wataru; Abe, Takaya; Itai, Kazuyoshi; Ogasawara, Kuniaki; Omama, Shinichi; Turin, Tanvir Chowdhury; et al. (Journal of epidemiology, 2016)
While it is assumed that dialysis patients in Japan have a higher prevalence of atrial fibrillation (AF) than the general population, the magnitude of this difference is not known. Standardized prevalence ratios (SPRs) for AF in dialysis patients (n = 1510) were calculated compared to data from the general population (n = 26 454) living in the same area. The prevalences of AF were 3.8% and 1.6% in dialysis patients and the general population, respectively. In male subjects, these respective values were 4.9% and 3.3%, and in female subjects they were 1.6% and 0.6%. The SPRs for AF were 2.53 (95% confidence interval [CI], 1.88-3.19) in all dialysis patients, 1.80 (95% CI, 1.30-2.29) in male dialysis patients, and 2.13 (95% CI, 0.66-3.61) in female dialysis patients. The prevalence of AF in dialysis patients was twice that in the population-based controls. Since AF strongly contributes to a higher risk of cardiovascular mortality and morbidity in the general population, further longitudinal studies should be conducted regarding the risk of several outcomes attributable to AF among Japanese dialysis patients.